1997
DOI: 10.1093/oxfordjournals.aje.a009295
|View full text |Cite
|
Sign up to set email alerts
|

Proxy Reporting in Five Areas of Functional Status: Comparison with Self-Reports and Observations of Performance

Abstract: Proxy ratings of functional status were compared with subject self-reports in five domains relevant to the study of older persons and with observations of subject performance in two areas (physical and instrumental functioning). Data were derived from 233 proxy-subject pairs evaluated in a prospective study of hip fracture patients aged 65 years or more in Baltimore, Maryland (1990-1991). Agreement between proxy and subject reports was highest for a summary measure of instrumental functioning and lowest for a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
171
3
4

Year Published

2000
2000
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 199 publications
(184 citation statements)
references
References 52 publications
6
171
3
4
Order By: Relevance
“…In general, the greater the significant other's contact or involvement with the patient the better the agreement (25,26). Greater involvement can be expected to increase knowledge of the patient and therefore enhance the accuracy of ratings.…”
Section: Patient and Proxy Ratings Of Patient Qlmentioning
confidence: 99%
“…In general, the greater the significant other's contact or involvement with the patient the better the agreement (25,26). Greater involvement can be expected to increase knowledge of the patient and therefore enhance the accuracy of ratings.…”
Section: Patient and Proxy Ratings Of Patient Qlmentioning
confidence: 99%
“…8 Although proxy respondents are known to overestimate disability, this effect is small for observable activities such as mobility. 9 We felt it was important to include respondents who used a proxy as they represent the most vulnerable older adults. Access to the MCBS data was obtained through a data use agreement with CMS, and the study was approved by the University of Pittsburgh Institutional Review Board.…”
Section: Introductionmentioning
confidence: 99%
“…The literature consistently shows that family proxies report worse health-related quality of life (HRQOL) and functioning for conditions such as stroke (3, 4), cancer (5), dementia (6, 7), and general health conditions (8) when compared to self-report measures from patients. Although several studies have shown that mild to moderately impaired patients with dementia can provide reliable self-report information about their health and well-being (6, 9-11), family members are frequently viewed as the primary source of patient status information (12).…”
Section: Introductionmentioning
confidence: 99%